Feminisme dan Keadilan Reproduktif: Mempersoalkan Aborsi Berdasarkan Pengalaman Aktivisme HKSR - Abby Boangmanalu; Asri Pratiwi Wulandari (Jurnal Perempuan, 2023)
In Indonesia, abortion is categorized as an illegal and criminal act. Even though abortion due to medical indications and rape are exempt from criminal status, access to legal abortion is still almost impossible. Therefore, discussion about legal abortion and safe abortion cannot be done separately, for the criminalization of abortion is one of the factors behind unsafe abortions. Through focused discussions with 20 women activists representing civil society organizations who advocate for gender justice and SRHR in Indonesia, this research aims to document and reflect critically on the situation of reproductive injustice in the issue of abortion in Indonesia using a feminist lens. Building this research within the framework of reproductive justice thinking based on feminist praxis, we selected women activists as our informants. SRHR activists are the closest to and the most involved subjects in the feminist praxis of promoting reproductive justice, particularly on the issue of abortion